2007
DOI: 10.1007/s11146-007-9016-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Real Estate Investment under an Asymmetric Duopoly

Abstract: This paper examines the sub-game equilibrium strategies for a duopoly real option model consisting of two firms with asymmetric demand functions. The relative strength of the firms is found to have significant impact on the firms’ equilibrium strategies. Preemptive strategies are critical if difference in strength between the two competing firms is relatively small. Short bursts and recession induced overbuilding are two outcomes in the asymmetric duopoly model. The model, however, predicts that the two phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In this literature it is reported that if there are unanticipated changes in the hotel market, such as from an economic downturn, then a strategy of high capital spending may fail to deliver targeted increases in revenue and property values (Williams, 1997;Wong & Norman, 1994). When the hotel property market is depressed or experiencing extreme levels of volatility, the preferred capital spending strategy will be to defer property acquisitions (Chu & Sing, 2007). Application of this strategy has to be weighed, however, against any competitive disadvantage resulting from a competitor securing first mover advantage resulting from pre-emptive market entry (Grenadier, 2002;Wang & Zhou, 2006;Williams, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this literature it is reported that if there are unanticipated changes in the hotel market, such as from an economic downturn, then a strategy of high capital spending may fail to deliver targeted increases in revenue and property values (Williams, 1997;Wong & Norman, 1994). When the hotel property market is depressed or experiencing extreme levels of volatility, the preferred capital spending strategy will be to defer property acquisitions (Chu & Sing, 2007). Application of this strategy has to be weighed, however, against any competitive disadvantage resulting from a competitor securing first mover advantage resulting from pre-emptive market entry (Grenadier, 2002;Wang & Zhou, 2006;Williams, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Where a hotelier feels exposed to such a competitive threat, irrational over-expenditure on building infrastructure can result (Grenadier, 2002). Chu and Sing (2007) note that when the hotel property market is strong, there is a greater incentive for owners to increase their capital expenditures. Insights from the empirical findings reported herein suggest these studies have been conducted from a somewhat generalised perspective, however, as they fail to recognise different expenditure strategies employed by different hotel owner types.…”
Section: Discussionmentioning
confidence: 99%
“…II,J 2) = P,IQ'I = P,J a , -b p,I +c P WI)y( t) II ", ( 2) = �'IQ"I = �'I (a w -b�" + CP'I) Y(t ) (8) The price responsive functions developers are respectively given by:…”
Section: B Competition{orm and Demandfunctionsmentioning
confidence: 99%
“…The model mainly explained why some real estate markets may experience building booms when facing a declining demand and property value. However, Chu and Sing (2007) [8] pointed out that in the duopoly model of Grenadier (1996) and Grenadier (2002) [9] , a firm did not have advantages over the other, and who will become the leader or follower of the game did not affect the equilibrium results.…”
Section: Introductionmentioning
confidence: 99%
“…Grenadier [7] provides a tractable approach for deriving equilibrium investment strategies in a continuous-time Cournot-Nash framework and obtains the impact of competition drastically eroding the value of the option to wait and lead to investment at near the zero net present value threshold. Chu and Sing [8] consider the subgame equilibrium strategies for a duopoly real option model with asymmetric demand functions and find that the relative strength of the firms has significant impact on the firms equilibrium strategies. Kong and Kwok [9] examine strategic investment games between two firms which compete for optimal investment under uncertain revenue flows in a duopoly market with negative externality and positive externality.…”
Section: Introductionmentioning
confidence: 99%